RUMAH GAYA ARSITEKTUR MINIMALlS di YOGYAKARTA . - Sugestiyadi, Bambang (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
ABSTRACT Yogyakarta could be the mirror of "Nusantara" since it had been accumulated with people from all around the Nusantara for education. It gradually grow into semi metropolis city, where new physical facilities developed. There for physical facilities are needed. This research was conducted to know the minimalism architecture style implemented in house development in Yogyakarta. The research was’ carried out on qualitative design. Data is collected through observation, visualization, skates maker, photo documentation and deeply interview. Relevant documentation from other connected departments was taken. Data is analyzed with inductive method: it does not mean to reveal hypothesis but it is focused to make an abstract. Triangulation was conducted to test data validity. The results showed that: (a) House and housing development until 2004 decade still dominated by Mediteran Style, Tropical House Style and Classical House Style with ornaments, (b) The Minimalism House Style in architecture focuses on essential and functional aspects. The Minimalism Style dominated by basic geometrical forms without ornament or decoration; It began to grow since 2004 to 2006, in Sleman Regency, Yogyakarta. Keywords: Architecture Style, Development, Minimalism Architecture Style.